Starting ART following cryptococcal meningitis:The optimal time has yet to be defined - T A Bicanic; J N Jarvis; A Loyse; T S Harrison (AOSIS, 2013)
Ever since the public sector rollout of antiretroviral therapy (ART) in 2004, the question of the optimal time to start ART following diagnosis of an opportunistic infection has aroused controversy among South African HIV clinicians and researchers.